The influence of TikTok marketing on consumer purchase intention among students / Nurazree Mahmud … [et al.] - Mahmud, Nurazree; Yaakob, Ahmad Mirza Nabil; Abd Majid, Nurul Ain; Nurulzlan, Nur Afrina; Khairil, Nur Husnina (Faculty of Art and Design, 2024)
TikTok marketing has an enormous and broad effect on the purchasing intentions of students. TikTok has become an extremely effective medium for marketers to connect with consumers due to its interesting and simple-to-read content structure. TikTok's algorithmic content distribution system is designed to draw in users and market a range of goods and services. This study looks into how TikTok marketing affects students' intentions to buy at selected Malaysian higher education institutions. The growing popularity of TikTok as a social media platform, especially among young people, emphasises the need to comprehend its influence on consumer behaviour. In this study, a quantitative methodology was applied, and analytical approaches employed, including reliability analysis and multiple regression analysis. The study concentrated on three important variables that affect consumers' intentions to buy: brand awareness, product quality, and price. A total of 115 respondents from the chosen universities took part in responding to the sent questionnaire. The research aims to offer insights into how businesses may effectively exploit the platform to engage with students as consumers by looking at these aspects in the context of TikTok marketing. The findings show that TikTok marketing has a major impact on student purchase behaviour, with product quality and price having a major influence on intentions to buy. All things considered, this study deepens our knowledge of how TikTok affects consumer behaviour, especially among students. It demonstrates the platform's potential as an ideal instrument for engaging students as customers and provides important insights for businesses trying to maximise their TikTok marketing efforts. Future studies on the evolving landscape of social media marketing and its effects on customer behaviour under various conditions can build on this research